ナンキョク・ショウワ キチ デ カンソク サレタ ヒョウシン - 神沼, 克伊; カミヌマ, カツタダ; 羽田, 敏夫; ハネダ, トシオ; KAMINUMA, Katsutada; HANEDA, Toshio (国立極地研究所, 1979)
P(論文) 1976年2月から1977年1月まで,南極・昭和基地の地震観測網で観測した氷震について調べた.見かけ上氷震は,1)立ち上がりの明りょうな記象,2)立ち上がりの不明りょうな記象,3)群発氷震,の3種類に分けられる.このうち1),2)をそれぞれI型,II型とする.I型は1年間に80000回以上も発生しており,冬季に多い.また,これまで観測された氷震が気温の下降時に発生しているのに対し,I型は気温とは無関係に発生している.また,潮汐との顕著な関係も認められない.II型は約80回発生しているが夏に多く,昭和基地の大陸側から到来することから,大陸氷床の崩壊または,氷山生成に伴う破壊と考えられる.3)の群発氷震は,冬季にのみ発生し,その発生時間も,1日のうち気温変化の大きな夜間に集中していることから,熱歪による体積変化が原因であろう. Three types of icequakes were observed by the tripartite seismological network at Japanese Antarctic station, Syowa during the period from February 1976 to January 1977. The types are (1) shocks with a sharp initial phase (named Type I), (2) shocks with a small or unidentified amplitude of initial phase (named Type II), and (3) swarms. More than 80000 shocks of Type I and about 80 of Type II occurred through the year. A large number of shocks of Type I occurred in the austral winter season, whereas the number of Type II shocks was larger in summer than in winter. No correlations are identified between the icequake occurrence and the air temperature change, and between that and the sea level change. The features of icequakes suggest that the shocks of Type II are caused by fractures in the ice near the shelf edge of ice sheet, giving rise to the calving of icebergs and so on. Swarms are estimated to be caused by the temperature changes. departmental bulletin paper